Effect of Cyberlindnera jadinii supplementation on growth performance, serum immunity, antioxidant status, and intestinal health in winter fur-growing raccoon dogs (Nyctereutes procyonoides) - Zhao, Dehui; Zhang, Haihua; Liu, Keyuan; Wu, Yan; Zhang, Borui; Ma, Cuiliu; Liu, Hanlu (Frontiers in Veterinary Science, 2023)
This study aimed to investigate the effects of Cyberlindnera jadinii supplementation on the growth performance, nutrient utilization, serum biochemistry, immunity, antioxidant status, and intestinal microbiota of raccoon dogs during the winter fur-growing period. Forty-ﬁve 135 (±5) day-old male raccoon dogs were randomly assigned to three dietary groups supplemented with 0 (group N), 1 × 109 (group L) and 5 × 109 CFU/g (group H) Cyberlindnera jadinii, with 15 raccoon dogs per group. The results showed that Cyberlindnera jadinii in groups L and H improved average daily gain (ADG) and decreased feed-to-weight ratio (F/G) (P < 0.05). No significant difference was found in nutrient digestibility and nitrogen metabolism among the three groups (P > 0.05). Compared with group N, serum glucose levels were lower in groups L and H (P < 0.05). The levels of serum immunoglobulins A and G in group L were higher than those in the other two groups (P < 0.05), and the levels of serum immunoglobulins A and M in group H were higher than those in group N (P < 0.05). Supplementation with Cyberlindnera jadinii in groups L and H increased serum superoxide dismutase activity, and the total antioxidant capacity in group H increased compared with group N (P < 0.05). The phyla Bacteroidetes and Firmicutes were dominant in raccoon dogs. The results of principal coordinate analysis (PCoA) showed that the composition of microbiota in the three groups changed significantly (P < 0.05). The relative abundance of Campylobacterota was increased in the H group compared to the N and L groups (P < 0.05). The relative abundance of Sarcina was increased in group L compared with the other two groups (P < 0.05), while the relative abundance of Subdoligranulum and Blautia were decreased in group H compared with the other two groups (P < 0.05). Also, the relative abundance of Prevotella, Sutterella and Catenibacterium was higher in group L (P < 0.05) compared with group H. In conclusion, dietary supplementation with Cyberlindnera jadinii improved growth performance, antioxidant activity, immune status, and improved intestinal microbiota in winter fur-growing raccoon dogs.